Trend Penggunaan Media Sosial Dalam Industri Pariwisata Di Kota Batam - Saut Pintubipar Saragih; Yuli Siyamto (LPPM Universitas Putera Batam, 2018)
The existence of social media in the era of information technology especially in tourism industry is very profitable for the perpetrators of the tourism industry because it can be used more effectively and efficiently in the delivery of information to tourists or potential visitors. In this research will be examined how the business entrepreneurs, operators or managers optimise and use social media application platform in increasing tourist visits, increasing popularity and eventually increasing the economic income. In this study, researcher team used descriptive research method where researchers want to find the facts that exist on the utilization of social media applications by entrepreneurs in the field of tourism. through this research method is expected discovery that can explain related to the benefits gained by users of social media in the tourism industry in the city of Batam. The result of this research is that based on the data obtained and processed shows that entrepreneurs in tourism have used multi platform social media. Social media applications used include facebook (100%), Instagram (87.5%), twitter (46.8%), whatsapp (97.3%), youtube (28.1%), Line (15, 6%) and other applications (3%). Further data shows that entrepreneurs or tourism operators and even managers have taken advantage of social media applications by having separate accounts for their tourism purpose, instead of the other data show that not all them have premium or business accounts for this tourism business.